Teacher PAI's Strategy In Growing Social Caring Character Among Junior High School Students - Amalia, Adila; Rangkuti, Miswar (Institut Agama Islam An-Nawawi Purworejo, 2025)
This research aims to determine the strategies used by Islamic Religious Education (PAI) teachers in cultivating social caring character among junior high school students. This research uses a qualitative approach by producing descriptive data. Data collection techniques include interviews, observation and documentation. The results of the research show that PAI teachers at Al-Hidayah Middle School in Medan foster students' social caring character through providing motivation, input and positive direction for the students' future. Obstacles faced include limited time, lack of student discipline, and low student motivation. To overcome these obstacles, PAI teachers collaborate with other subject teachers to provide role models and teaching that strengthens the character of social care, both in the school environment and outside of school. Apart from that, teachers also play an active role in motivating students to improve their social care character. The impact of this research shows the importance of the strategic role of PAI teachers in forming students' characters who care more about each other, so that they can create a school environment that is more inclusive, harmonious, and supports the formation of a young generation who has high social awareness. These findings can be a guide for other schools in designing learning programs that are integrated with strengthening social care characters.